2009
DOI: 10.4137/cmt.s2983
|View full text |Cite
|
Sign up to set email alerts
|

Experience with Cinacalcet for Secondary Hyperparathyroidism in Patients with Chronic Kidney Disease Stage III and IV

Abstract: Dysequilibrium in calcium and phosphate metabolism with development of secondary hyperparathyroidism (SHPT) is common in patients with chronic kidney disease (CKD) stage III and IV. Dietary phosphate restrictions and calcium based oral phosphate binders have not been effective in all subjects with SHPT, and soft tissue and vascular calcifications with an increased risk of cardiovascular death related are known consequences. Treatment with the calcimimetic Cinacalcet (Cc) has contributed to a better calcium and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 24 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…This has been argued by other authors to support the use of cinacalcet in patients with stage 3–4 CKD 13 . In a retrospective study of 10 patients with CKD in stage 3 or 4 with SHPT resistance to treatment, the administration of cinacalcet was associated with a significant decrease in serum calcium concentration at month 3 and a subsequent normalization after 9 months of cinacalcet treatment 19 …”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…This has been argued by other authors to support the use of cinacalcet in patients with stage 3–4 CKD 13 . In a retrospective study of 10 patients with CKD in stage 3 or 4 with SHPT resistance to treatment, the administration of cinacalcet was associated with a significant decrease in serum calcium concentration at month 3 and a subsequent normalization after 9 months of cinacalcet treatment 19 …”
Section: Discussionmentioning
confidence: 82%
“…13 In a retrospective study of 10 patients with CKD in stage 3 or 4 with SHPT resistance to treatment, the administration of cinacalcet was associated with a significant decrease in serum calcium concentration at month 3 and a subsequent normalization after 9 months of cinacalcet treatment. 19 Hyperphosphataemia has been considered the most worrisome complication of cinacalcet treatment in pre-dialysis patients. 10,11 Increased serum phosphate levels have been Cinacalcet in pre-dialysis patients associated with an increased risk of vascular calcifications and death in patients with end-stage renal disease 20,21 as well as an increased mortality risk among patients with CKD who are not on dialysis.…”
Section: Discussionmentioning
confidence: 99%
“…46 The other two studies concluded that special attention should be paid to the frequent occurrence of hypocalcemia and long-term hyperphosphatemia in CKD stage III and IV patients receiving cinacalcet. 47,48 Most notably, pronounced hyperphosphatemia represents a serious complication which may occur during treatment with cinacalcet in these patients. As possible causes for these elevated P levels, changes of two substances promoting urinary P excretion (phosphatonins) have to be taken into consideration: fibroblast growth factor 23 (FGF-23) and PTH.…”
Section: Ckd and Bone Healthmentioning
confidence: 99%
“…Three clinical studies have indicated significant cinacalcet-induced increases of serum P levels. [46][47][48] Charytan et al reported a phase II, randomized, doubleblind, placebo-controlled, 18-week study of cinacalcet administered to predialysis patients. The doses of cinacalcet administered ranged from 30 to 180 mg/day and the mean serum intact PTH levels decreased by 32% in these patients, while they increased by 6% in the placebo group.…”
Section: Ckd and Bone Healthmentioning
confidence: 99%
“…Recently Foluslund et al reported efficacy of cinacalcet for severely advanced 2HPT in patients with CKD stage 3-4 who did not tolerate for PTx. 3 In patients with CKD stage 3-4 who suffer from severely advanced 2HPT which cannot be controlled by usual medical treatment or PTx, cinacalcet can be a useful candidate for managing 2HPT.…”
mentioning
confidence: 99%